c - Spiegel, Murray R.; Stephens, Larry J. (New York ; McGraw-Hill Education, 2018)
Tough Test Questions? Missed Lectures? Not Enough Time? Textbook too pricey? Fortunately, there's Schaum's. This all-in-one-package includes more than 500 fully-solved problems, examples, and practice exercises to sharpen your problem-solving skills. Plus, you will have access to 25 detailed videos featuring math instructors who explain how to solve the most commonly tested problems--it's just like having your own virtual tutor! You'll find everything you need to build confidence, skills, and knowledge for the highest score possible. More than 40 million students have trusted Schaum's to help them succeed in the classroom and on exams. Schaum's is the key to faster learning and higher grades in every subject. Each Outline presents all the essential course information in an easy-to-follow, topic-by-topic format. Helpful tables and illustrations increase your understanding of the subject at hand. Schaum's Outline of Geometry, Sixth Edition features: * Over 500 problems, solved step by step * Updated content to match the latest curriculum * An accessible format for quick and easy review * Clear explanations for key concepts * Access to revised Schaums.com website and new app with access to 25 problem-solving videos, and more.--
Variables and graphs -- Frequency distributions -- The mean, median, mode, and other measures of central tendency -- The standard diviation and other measures of dispersion -- Moments, skewness, and kurtosis -- Elementary probability theory -- The binomial, normal, and poisson distributions -- Elementary sampling theory -- Statistical estimation theory -- Statistical decision theory -- Small sampling theory -- The chi-square test -- Curve fitting and the method of least squares -- Correlation theory -- Multiple and partial correlation -- Analysis of variance -- Nonparametric tests -- Statistical process control and process capability.
Includes index.
Keywords: Mathematical statistics -- Outlines, syllabi, etc; Mathematical statistics -- Problems, exercises, etc; Statistics -- Problems, exercises, etc; STUDY AIDS -- Tests (Other); Statistics; Mathematical statistics; Outlines and syllabi; Problems and exercises